2022
DOI: 10.1371/journal.pone.0273502
|View full text |Cite
|
Sign up to set email alerts
|

“I feel like I’m in a revolving door, and COVID has made it spin a lot faster”: The impact of the COVID-19 pandemic on youth experiencing homelessness in Toronto, Canada

Abstract: Purpose Research has shown that youth experiencing homelessness (YEH) face barriers to social inclusion and are at risk for poor mental health. With the COVID-19 pandemic threatening the health, wellbeing, and economic circumstances of people around the world, this study aims to assess the impacts of the pandemic on YEH in Toronto, Ontario, as well as to identify recommendations for future waves of COVID-19. Methods Semi-structured interviews were conducted with YEH (ages 16–24, n = 45) and staff who work in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The five studies that explored the difficulties Black Canadians faced during the pandemic as a result of systemic racism and discrimination determined that the difficulties study participants experienced accessing COVID-19-related health care might have been exacerbated by existing stress stemming from racism, systematic bias and barriers, and socioeconomic vulnerabilities. 40 , 46 - 49 The significant link between police cruelty towards Black people in Canada, increased rates of COVID-19 in the Black population and the correlation of lower socioeconomic status, lower level of education and lower-paying employment with great risk of exposure to COVID-19, serves as a symbol of the continuing and historical racism experienced by Black people. 46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five studies that explored the difficulties Black Canadians faced during the pandemic as a result of systemic racism and discrimination determined that the difficulties study participants experienced accessing COVID-19-related health care might have been exacerbated by existing stress stemming from racism, systematic bias and barriers, and socioeconomic vulnerabilities. 40 , 46 - 49 The significant link between police cruelty towards Black people in Canada, increased rates of COVID-19 in the Black population and the correlation of lower socioeconomic status, lower level of education and lower-paying employment with great risk of exposure to COVID-19, serves as a symbol of the continuing and historical racism experienced by Black people. 46 …”
Section: Resultsmentioning
confidence: 99%
“…The quantitative study conducted by Noble et al 49 revealed that systemic racism and the COVID-19 pandemic exacerbated mental distress among Black youth experiencing homelessness in Toronto, with barriers to securing employment and landlords’ racial discrimination making it difficult to obtain accommodation.…”
Section: Resultsmentioning
confidence: 99%
“…Research on this topic suggests their predictions were borne out. The COVID-19 pandemic reduced access to services, employment, and housing for youth experiencing homelessness, while simultaneously increasing their social isolation, mental health distress, and substance use, particularly among youth who identified as Black, Two-Spirit, Lesbian, Gay, Bisexual, Transgender, Queer or Questioning and additional sexual orientations and gender identities (2SLGBTQ+), or as newcomers in Canada (Dej et al, 2022;Noble et al, 2022). Homeless youth also reported job loss and income disruption, increased substance use, as well as mental health and relationship deterioration throughout the COVID-19 Pandemic (Rew et al, 2021;Tucker et al, 2020).…”
Section: Health Inequities Covid-19 and Homelessnessmentioning
confidence: 99%
“…Interviews with nine Inuit youth leaders in Nunavut, Canada, an Arctic community, focused on how the pandemic impacted their engagement with I-SPARX, an Inuit specific e-intervention designed to build resilience in mental health (19). Nobel et al (20) interviewed homeless youth about the unique structural and psychosocial challenges they faced during an extended pandemic. Our study was designed to broadly explore how the extended pandemic and public health measures to reduce viral spread impacted YYAs in Ontario Canada, examining impacts to the foundations they build their futures upon: relationships, education, employment, and important transitional events, as well as how they coped with all the changes.…”
Section: Introduction Backgroundmentioning
confidence: 99%